Communication Interaction Between Traders in Cultural Analysis (Case Study of Halat Traditional Market, Matsum City, Medan City) - Maisarah, Rizka; Zuhriah, Zuhriah (Lembaga penelitian dan pengabdian kepada Masyarakat, 2023)
The purpose of this study was to describe and analyze how people from different ethnic backgrounds interact with each other while doing business at Matsum City Halat Traditional Market. This research is a qualitative descriptive research, therefore the research method used in this study reflects this. The type of data presented through observation and interviews using primary data is the source of informant data. The sources of this informant data include traders at Matsum City Halat Traditional Market, books and journals that can be downloaded from the internet, and several documentation files that can be obtained directly at Matsum City Halat Market. Huberman and Johnny Saldana are the ones who will be able to get qualitative data analysis with an interactive model developed by Matthew B. Miles and A. Michael. This method of analysis was chosen for use in this particular study. The findings of this study show that the utilization of convection and divergence communication tactics is accurate whenever these traders engage in conversation with each other. Based on an analysis of 6 speakers' linguistic, idiomatic, intonational, mental, and gestural approaches to their interactions, we found that 4 (four) traders often use convergence communication tactics indirectly. The other two people use different communication strategies in their contacts, which means they don't seek to change their innate attitudes or behaviors when engaging with others.